Տեսողության խանգարումներ ունեցող նախադպրոցականների տարածական կողմնորոշման կարողությունների ձևաորման տեսական հիմնավորումն ընտանիքում - Դավթյան, Ս․ Ռ․
В статье представлены средства и методы обучения пространственной ориентировки дошкольников с нарушениями зрения в условиях семьи. Показана эффективность раннего обучения этих детей умениям и навыкам ориентировке в пространстве. The following article presents the contents of the teaching process of orientation skills in environment for pre-school-aged children with visually impairments in family. The teaching process is directed towards the expansion of the children’s word outlook and the formation of the objective concept existing in the environment.
Keywords: Դաստիարակություն